Could It Be Pneumonia? Lung Ultrasound in Children With Low Clinical Suspicion for Pneumonia. Issue 4 (July 2020) - Scheier, Eric; Levick, Nadine; Peled, Julia; Balla, Uri
Abstract : Background: Community-acquired pneumonia (CAP) is a significant cause of pediatric morbidity and mortality worldwide. Emergency department point of care ultrasound (POCUS) is a first-line modality for diagnosis of CAP. The current coronavirus disease 2019 pandemic creates a unique opportunity to incorporate lung POCUS into the evaluation of a broader range of children. It has increased the utility of lung POCUS in both evaluation and follow-up of pediatric coronavirus cases. An increased use of lung POCUS creates an opportunity for earlier diagnosis while allowing the opportunity for overdiagnosis of small infiltrates and atelectasis. We collated a case series to demonstrate the benefit of lung POCUS in a very broad range of children. Methods: We collected a case series of 5 patients between December 2018 and December 2019 who presented nonclassically and were diagnosed with CAP on POCUS by a pediatric emergency physician. Conclusion: Routine lung POCUS in ill children will allow treating physicians to identify and follow a pulmonary infiltrate consistent with CAP quickly. We anticipate that early and more frequent use of POCUS and earlier diagnosis of CAP may improve outcomes by decreasing healthcare encounters within the same illness and by reducing the incidence of late sequelae of pneumonia such as empyema and effusions. However, we acknowledge that this may come at the expense of the overtreatment of viral infiltrates and atelectasis. Further study is required to improve the specificity of lung POCUS in the evaluation of CAP. Abstract : Supplemental Digital Content is available in the text.